Fare well, Illyria - Binder, David (Central European University Press, 2013)
As a reporter for the prestigious New York Times the author interviewed many of the leading political figures of the Balkans (Illyria). He also sought out the area's intellectuals, many of them critical of their leaders, and everyday people who provide a sense of daily life. He devotes a chapter to each ethnic group from Vlachs to Serbs, talks about their differences and similarities, and does so without giving offense. He also provides a short historical account of the various places he visits, which deepens our understanding of the local cultures. The reader meets people from all walks of life: politicians, poets, literary and art critics, journalists, handymen, car mechanics, fishermen and farmers. From Milovan Djilas and Nicolae Ceausescu to Markos Vafiadis and Sali Berisha to the Serbian "majstor" Misha and an un-named Bosnian bar singer, Binder's book features a remarkable gallery of people whose presence contributes authenticity and human warmth to the narrative